2006
DOI: 10.1161/01.str.0000209240.63821.1a
|View full text |Cite
|
Sign up to set email alerts
|

d -Dimer Predicts Early Clinical Progression in Ischemic Stroke

Abstract: Background and Purpose-Plasma D-dimer levels, measured using a research laboratory assay, independently predict progressing ischemic stroke. We wished to confirm these findings using commercially available assays and to provide data to allow the design of intervention studies. Methods-We studied 219 consecutive acute ischemic stroke admissions of whom 54 (25%) met criteria for progressing stroke. Results-There were strong correlations between D-dimer results as measured by the Biopool AB, MDA and VIDAS assays;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(30 citation statements)
references
References 11 publications
3
26
1
Order By: Relevance
“…14 D-dimer is known to be positively associated with coronary heart disease incidence 18,19 and its recurrence, 20 which is largely independent of conventional risk factors. 21 D-dimer has also been shown to predict early clinical progression in ischemic stroke 22,23 and poor functional outcome after acute spontaneous intracerebral hemorrhage 24 and subarachnoid hemorrhage. 25 There are several plausible mechanisms through which D-dimer levels could be closely related to ERILs.…”
Section: Discussionmentioning
confidence: 99%
“…14 D-dimer is known to be positively associated with coronary heart disease incidence 18,19 and its recurrence, 20 which is largely independent of conventional risk factors. 21 D-dimer has also been shown to predict early clinical progression in ischemic stroke 22,23 and poor functional outcome after acute spontaneous intracerebral hemorrhage 24 and subarachnoid hemorrhage. 25 There are several plausible mechanisms through which D-dimer levels could be closely related to ERILs.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown elevated D-dimer levels during the acute phase of stroke, which eventually fall 14,26,30,34) . However, previous studies have demonstrated only that plasma D-dimer levels predict a progressing ischemic stroke 4,5) . We studied the relationship between D-dimer level and infarction volume and the relationship between D-dimer change and clinical outcome in AIS.…”
Section: Introductionmentioning
confidence: 95%
“…Limited data are available on coagulation markers very early after symptom onset, as the majority of previous studies were performed >12 h after symptom onset [3,5,6,7,8,10,11,12,13,14]. D-dimer levels have been shown to be associated with cardioembolic strokes [4,6,7,8,9,10,12,14], yet their significance in acute stroke remains to be determined.…”
Section: Introductionmentioning
confidence: 99%